The Effect of Dysmenorrhea Exercise on Reducing Mild Dysmenorrhea Pain and Anxiety in Adolescent Girls - Tina Santika; Uci Ciptiasrini; Madinah Munawaroh (Jurnal Maternitas Kebidanan, 2026)
Dysmenorrhea is a common condition experienced by adolescent girls during menstruation. This condition is usually characterized by pain in the lower abdomen that can be accompanied by other symptoms such as nausea, headaches, fatigue, and mood swings. In addition to physical symptoms, dysmenorrhea can also affect adolescents' psychological state, one of which is increased anxiety levels. Non-pharmacological treatments such as dysmenorrhea exercises can be an alternative to reduce pain and anxiety. This study aims to determine the effect of dysmenorrhea exercises on reducing mild dysmenorrhea pain and anxiety in adolescent girls. The study used a quantitative approach with a quasi-experimental one-group pretest-posttest design. The study sample consisted of 25 adolescent girls selected using a total sampling technique. The results showed that before the dysmenorrhea exercise intervention, all participants (100%) experienced mild pain. After the intervention, the majority of respondents (84%) no longer felt pain and 16% still experienced mild pain. Meanwhile, before the intervention, the majority of respondents (55%) experienced moderate anxiety, and after the intervention, the majority (64%) experienced mild anxiety. Statistical analysis using the Wilcoxon test showed a significant reduction in pain levels (Z = -4.690; p = 0.000) and anxiety levels (Z = -4.796; p = 0.000). In conclusion, dysmenorrhea exercises effectively reduced the intensity of mild dysmenorrhea pain and anxiety levels in adolescent girls at Doa Bangsa Vocational School.